Comparative study on selective laser sintering of aromatic and aliphatic thermoplastic polyurethanes: processability, microstructure, and mechanical properties - Zhou, Meixin (2023)
Selective laser sintering (SLS) of thermoplastic polyurethane (TPU) has attracted tremendous interest in producing prototypes and end-use parts for applications in mechanical energy absorption, biomedical scaffold, and wearable electronics because of the versatile properties of this material. This work aims to reveal the effects of the chemical structure on the SLS processability of TPU powders as well as the microstructure and mechanical properties of their SLS-printed parts. It was found that the aliphatic TPU exhibited better SLS processability and lower total porosity than the aromatic TPU because of its flexible polymer chains. In contrast, the aromatic TPU displayed higher tensile strength and mechanical energy absorption because of its rigid polymer chains and the increased intermolecular force. Pores in the SLS-printed parts were classified based on their morphological features, and their origins were investigated via X-ray computed tomography. This study provides guidance for the design, selection, and optimization of TPU powders for the SLS process according to different applications.